Pengaruh Penguasaan Technological Pedagogical and Content Knowledge (TPACK) Calon Guru Ekonomi Terhadap Kemampuan Menyusun Lesson Plan Berbasis Kurikulum Merdeka - Aulia Rahma Yuliananda; Trisno Martono; Feri Setyowibowo (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the influence pre-service economics teachers' mastery of Technological Pedagogical and Content Knowledge (TPACK) on the preparation of Independent Curriculum-based lesson plans. The research method used is quantitative with a population of Sebelas Maret University Economics Education student class 2019 and 2020. The sampling technique used Simple Random Sampling with a sample size of 122 respondents. The results of this research show that (1) there is a positive and significant influence between Technological Content Knowledge (TCK) of prospective Economics teachers on the preparation of lesson plans based on the Independent Curriculum. (2) there is a positive and significant influence between the Technological Pedagogical Knowledge (TPK) of prospective Economics teachers on the preparation of lesson plans based on the Independent Curriculum. (3) there is a positive and significant influence between the Pedagogical Content Knowledge (PCK) of prospective Economics teachers on the preparation of lesson plans based on the Independent Curriculum. (4) there is a positive and significant influence between the Technological Pedagogical and Content Knowledge (TPACK) of prospective Economics teachers on the preparation of Independent Curriculum-based lesson plans.